2018
DOI: 10.1038/s41585-018-0035-8
|View full text |Cite
|
Sign up to set email alerts
|

Advances in laser technology and fibre-optic delivery systems in lithotripsy

Abstract: The flashlamp-pumped, solid-state holmium:yttrium-aluminium-garnet (YAG) laser has been the laser of choice for use in ureteroscopic lithotripsy for the past 20 years. However, although the holmium laser works well on all stone compositions and is cost-effective, this technology still has several fundamental limitations. Newer laser technologies, including the frequency-doubled, double-pulse YAG (FREDDY), erbium:YAG, femtosecond, and thulium fibre lasers, have all been explored as potential alternatives to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 115 publications
2
79
0
1
Order By: Relevance
“…The experimental Thulium fiber laser (TFL) is currently being studied as a potential alternative to the Holmium laser for treatment of kidney stones. Potential advantages of TFL technology have recently been reviewed in the literature [19,20]. While the majority of previous reports have been based on preliminary laboratory studies [21][22][23][24][25], the TFL has also shown promise in early clinical studies as well [26][27][28].…”
Section: Thulium Fiber Laser Lithotripsymentioning
confidence: 99%
“…The experimental Thulium fiber laser (TFL) is currently being studied as a potential alternative to the Holmium laser for treatment of kidney stones. Potential advantages of TFL technology have recently been reviewed in the literature [19,20]. While the majority of previous reports have been based on preliminary laboratory studies [21][22][23][24][25], the TFL has also shown promise in early clinical studies as well [26][27][28].…”
Section: Thulium Fiber Laser Lithotripsymentioning
confidence: 99%
“…Ultrafast pulsed fiber laser has been widely used in medical, spectral imaging, sensing, and processing fields in recent years by virtue of its high stability, good heat dissipation, and low cost . Passive operation of fiber laser via materials has recently been a hotspot which attracts enormous attention, especially in the field of communication .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast pulsed fiber laser has been widely used in medical, spectral imaging, sensing, and processing fields in recent years by virtue of its high stability, good heat dissipation, and low cost. [1][2][3][4][5][6][7] Passive operation of fiber laser via materials has recently been a hotspot which attracts enormous attention, especially in the field of communication. [8][9][10][11] On the one hand, mode locking based on the artificially saturable absorbers (SA): nonlinear polarization rotation mode-locking, nonlinear optical (NLO) loop mirror mode-locking, nonlinear multimode interference mode-locking, and material-mode-locking based www.advopticalmat.de carbon nanotubes (SWCNTs) can realize the tuning of modulation depth.…”
Section: Introductionmentioning
confidence: 99%
“…Thuliumdoped fiber lasers, erbium-doped fiber lasers, and Mid-IR hybrid lasers are suitable for this operation method. 6 Multiple systems of lasers are studied in some fields of medicine such as cancer treatment and tumor ablation, brain surgeries, epilepsy, cardiology and atrial fibrillation, lithotripsy, dermatology, skin rejuvenation, and lipolysis (see Figure 1). The energy of laser is a safe and effective tool for treating various cancers and the ablation of abnormal conductive pathways, for many reconstructive procedures and cosmetics.…”
Section: Introductionmentioning
confidence: 99%